STUDIES ON SOME ASPECT^ OF THE BIOLOGY OF THE COMMON ANCHOVY, THRISSOCLES MYSTAX (BLOCH & SCHNEIDER) - Venkataraman, G (Indian Journal of Fisheries, 2015)
The anchovies form an important fishery along the Malabar Coast and contributeconsiderably to the fish catches during certain seasons of the yearand especially during the lean years lor sardines. Of the 7 species ofanchovies recorded along the west coast, i,Thrissocles mystax is the mostcommon and is caught abundantly in the cdinmercial hauls. It has a widedistribution and is known to occur in the seas of India, Malay Archipelagoand China. It attains a maximum length of 205 mm.